Investment spending, equilibrium indeterminacy, and the interactions of monetary and fiscal policy - Thomas A. Lubik (The Johns Hopkins University, Department of Economics, 2003)
This paper investigates determinacy of equilibrium in a canonical New Keynesian model under different monetary and fiscal policy rules. It is shown that a simple monetary rule that responds aggressively to inflation is a necessary condition for equilibrium determinacy, when fiscal policy is accommodating. If there is a high degree of structural distortions in the economy, then the interesting possibility arises that both aggressive monetary and fiscal policies are required to guarantee existence. When investment adjustment costs are introduced, the monetary and fiscal policy dichotomy is in principle maintained. The determinacy region is, however, highly dependent on the degree of distortion in the economy. The more prices are sticky, and the less competitive firms are, the economy is likely to exhibit indeterminacy even if monetary policy is active.
Keywords: E22; E52; E63; 330; Indeterminacy; Investment; Monetary and Fiscal Policy; Neukeynesianische Makroökonomik; Geldpolitik; Finanzpolitik; Regelgebundene Politik; Investition; Anpassungskosten; Theorie; Gleichgewicht